Photoluminescence and X-ray photoelectron spectroscopic study of milled-ZnO material prepared by high energy ball milling technique - Wanichaya Mekprasart; Balaji R. Ravuri; Rattikorn Yimnirun; Wisanu Pecharapa (My University, 2020)
Luminescence properties that are correlated to near band edge emission and defect-related emission of milled zinc oxide (ZnO) powder prepared by high energy ball milling technique are investigated.Commercial ZnO powder (particle size of 525 nm) was chosen as starting material in milling process to produce ultrafine ZnO powder.The milling process was carried out at different speeds; 0, 200, 400 and 600 rpm for 10 min.After milling at high speed, change in color of milled ZnO powder was clearly observed that could be due to the defects in ZnO structure induced by mechanical strain during milling process.Surface morphology of milled ZnO powder was monitored by field-emission scanning electron microscopy (FESEM).Element component and surface chemical states of the samples were analyzed by X-ray photoelectron spectroscopy (XPS).Optical property of milled samples was investigated by diffuse reflectance UV-Vis spectrometer.Meanwhile, room-temperature photoluminescence spectroscopy of the milled samples was performed.The milled ZnO particle size was distinctly decreased to ca. 200 nm affirmed by FESEM images.Photoluminescence (PL) spectra of milled ZnO sample showed two prominent emission bands; UV and visible region.Visible emission intensity increased with increasing milling speed that would be attributed to greater structural defects caused by high mechanical strain during milling process.
Keywords: Ball (mathematics); ZnO doping and properties